Sustainable Ultrasound-Assisted Solid-Phase peptide synthesis (SUS-SPPS): Less Waste, more efficiency - Salvatore Mottola; Alessandra Del Bene; Vincenzo Mazzarella; Roberto Cutolo; Ida Boccino; Francesco Merlino; Sandro Cosconati; Salvatore Di Maro; Anna Messere (Ultrasonics Sonochemistry)
The integration of low-frequency ultrasound with Solid-Phase Peptide Synthesis (SPPS) was explored to establish a Sustainable Ultrasound-assisted Solid-Phase Peptide Synthesis (SUS-SPPS) method. This innovative approach significantly reduces solvent consumption, washing steps, time, and reagent usage compared to conventional manual SPPS protocols. The SUS-SPPS method exploits ultrasound at every stage of synthesis and work-up, reducing the process to just two steps. The first step sequentially combines Fmoc-amino acid coupling, capping of unreacted amino groups, and Fmoc deprotection into a single operation, while the second one consists of a single washing procedure. Moreover, we demonstrated that the method is compatible with various resin types, including Rink-amide, Wang, and Cl-Trt resins, and facilitates the efficient synthesis of peptides of varying lengths (up to 20-mers) and compositions, including those traditionally considered “difficult sequences”, with excellent yields and purity. Notably, SUS-SPPS reduces solvent usage per coupling cycle by 83–88%, marking a significant breakthrough in sustainable peptide synthesis.